WHEN NUMBERS REPRESENTED POVERTY: THE CHANGING MEANING OF THE FOOD RATION IN FRENCH COLONIAL AFRICA - (:unkn) unknown (My University, 2018)
This article examines the evolution of dietary knowledge about French colonial Africa, from the 1920s to the early 1950s. More specifically, it focuses on efforts to quantify daily food intake by tracing the different meanings assigned to nutrition over time. While such statistics were used as early as the 1920s to evaluate the food consumption of populations most useful to the imperial economy, it was only after the Second World War that they became a means of measuring living standards according to universal metrics. This history invites us to reflect on how poverty in Africa came to be recognized as a problem, by showing that such a process has neither been based entirely on social reality nor on the knowledge produced to delineate privation. Rather it also emerged from the changing set of meanings associated with this knowledge.
Keywords: African Research